PLATAFORMAS PARTICIPATIVAS DE AUXÍLIO À GESTÃO E PLANEJAMENTO URBANOS - Manso, Leonardo; Abiko, Alex; Leirner, André (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work, through a large and robust bibliographical revision, allowed some degree of organization of diffuse knowledge, in order to raise important requirements and guidelines for the development of technologies and platforms for citizen participation in city management, using information and communication technologies. The technological advances are challenging due to the high number of interconnected objects, and cover numerous aspects, such as architecture, scalability, data usage, security and privacy, governance, human factors, among others. Participatory platforms are aimed at driving sustainable urban and technological development, and improving the quality of life of citizens, by identifying the demands and guiding the provision of solutions to cities that are more sustainable, smart, resilient and responsive. This is only possible through technological and participation criteria and requirements, which must be taken into account to achieve its sustainability objectives. The exposed approach allows the development of innovative research, methods and products.